Regulation of Sexual Harassment in the Academic Environment - Katja Filipčič; Manja Skočir (Annales, Series Historia et Sociologia)
This article analyses the regulation of sexual harassment within the academic environment. It highlights that sexual harassment is addressed not only by legal regulations but also through codes of ethics. It demonstrates that sexual harassment is recognised as a violation of ethical norms and public ethics in the codes of many professional associations, yet it is also regulated by statutory laws, bylaws, and other general acts. The article examines the distinctions between the regulation of sexual harassment by codes of ethics and legal acts, and identifies the challenges in defining sexual harassment in accordance with the fundamental principles of criminal law. It further explores various forms of accountability relevant to members of the academic community. Finally, it discusses the role of internal regulations, providing insights into their structure and the regulation of sexual harassment within Slovenian higher education organisations.